2017
DOI: 10.3390/jfb8030035
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Comparison of Cortical and Hippocampal Neural Progenitor Morphology and Differentiation through the Use of Micro- and Nano-Topographies

Abstract: Neuronal morphology and differentiation have been extensively studied on topography. The differentiation potential of neural progenitors has been shown to be influenced by brain region, developmental stage, and time in culture. However, the neurogenecity and morphology of different neural progenitors in response to topography have not been quantitatively compared. In this study, the correlation between the morphology and differentiation of hippocampal and cortical neural progenitor cells was explored. The morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…[44][45][46] Moreover, other studies have shown that microtopography induces neural, cartilage, or even adipogenic trans-differentiation of hMSCs. [47][48][49][50][51] Consistently, we found that osteogenic differentiation of hMSCs was inefficient when microtopography alone was used. However, if chemical factors were used to determine the osteogenic lineage of hMSCs in advance, the osteogenic induction effect of microtopography was greatly improved.…”
Section: Discussionmentioning
confidence: 69%
“…[44][45][46] Moreover, other studies have shown that microtopography induces neural, cartilage, or even adipogenic trans-differentiation of hMSCs. [47][48][49][50][51] Consistently, we found that osteogenic differentiation of hMSCs was inefficient when microtopography alone was used. However, if chemical factors were used to determine the osteogenic lineage of hMSCs in advance, the osteogenic induction effect of microtopography was greatly improved.…”
Section: Discussionmentioning
confidence: 69%
“…We showed that when the pillar topography was applied at the maturation stage, it will not only result in increased branching as observed in a previous study 21 , but also enhances the maturation and changes electrophysiological properties of the neurons. In comparison, cortical neurons differentiated on gratings have been observed to display less branching 29 . Further evaluation on different feature sizes of the patterns may be performed to determine the optimal topographical dimensions for DA neuronal differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…In a morphometric analysis of differentiated cortical and hippocampal astrocytes derived from neural progenitor cells, cortical astrocytes displayed numerous short, well-defined projections with multiple branches per projection and smaller soma areas. In contrast, hippocampal astrocytes possess larger soma areas with few but long projections with almost no branching [31]. The distinctions in astrocytic projections, which is crucial for energy processing in support of neuronal metabolism through delivery of substrate from capillaries to synapse, may underlie the heightened energetic profile of cortical astrocytes compared to hippocampal astrocytes.…”
Section: Discussionmentioning
confidence: 99%